Computational complexity as a potential limitation on brain–behaviour mapping - Ozkirli, Ayberk; Herzog, Michael H.; Jastrzębowska, Maya A. (The European journal of neuroscience, 2025)
Within the reductionist framework, researchers in the special sciences formulate key terms and concepts and try to explain them with lower‐level science terms and concepts. For example, behavioural vision scientists describe contrast perception with a psychometric function, in which the perceived brightness increases logarithmically with the physical contrast of a light patch (the Weber‐Fechner law). Visual neuroscientists describe the output of neural circuits with neurometric functions. Intuitively, the key terms from two adjacent scientific domains should map onto each other; for instance, psychometric and neurometric functions may map onto each other. Identifying such mappings has been the very goal of neuroscience for nearly two centuries. Yet mapping behaviour to brain measures has turned out to be difficult. Here, we provide various arguments as to why the conspicuous lack of robust brain–behaviour mappings is rather a rule than an exception. First, we provide an overview of methodological and conceptual issues that may stand in the way of successful brain–behaviour mapping. Second, extending previous theoretical work (Herzog, Doerig and Sachse, 2023), we show that brain–behaviour mapping may be limited by complexity barriers. In this case, reduction may be impossible. Robust one‐to‐one mappings between the sensory stimulus and the behavioural level (top and bottom) do not imply that mappings can be found between the behavioural and the neural levels or the stimulus and neural levels, that is, within the inverted hourglass. For this reason, reduction from behaviour to brain processes to chemical and physical processes may be impossible.